Design and Development of a Database Using CDS/ISIS:An Analytico-Synthetic Classification Approach - Sarvamangala, G. (Journal of Information and Knowledge, 2014)
Database creation is an important area of microcomputer application. Several software packages are available for design and development of Bibliographic Databases. The CDS/ISIS in particular provides a versatile facility for creation of BDB. However the documentation of CDS/ISIS is not yet totally explicit and therefore bit complicated in its communication to users. In this paper an attempt is made to present instructions for database creation using Dr. S.R. Ranganathan's analytico-synthetic approach.